Estream: A mobile live streaming platform for esports - Lim, Yu Qi (2024)
In response to the rapid growth of esports and the ever-evolving landscape of live broadcasting platforms, this project endeavors to redefine the user experience within the esports community. To address common challenges in content discovery, community engagement, and profitability, this project aims to introduce a platform for transformative change beyond traditional video streaming methods. By leveraging state-of-the-art artificial intelligence (AI) technology and embracing the mobile-centric preferences of contemporary users, our platform, eStream seeks to provide a dynamic and immersive environment for esports enthusiasts. Through innovative content discovery mechanisms encompassing text, and images, as well as interactive donation features, users can support their favorite streamers, and this mobile app is dedicated to fostering a strong and inclusive sense of community. This project is steadfastly committed to pushing the boundaries of live broadcasting in the digital age, contribute in reshaping the esports landscape and nurturing unparalleled participation and connection among users.